The rise of neoliberalism and his criticism - Milić Slobodan (Ekonomski Signali, 2019)
The text is dealing with the demonstration of the rise of neoliberal ideology throughout the historical flows and thoughts of the authors who dealt with the problem of neoliberal doctrine. Neoliberal ideology becomes the only alternative to totalitarian systems of the last century, and neoliberalism becomes synonym to the paradigm of contemporary society. Despite the theoretical advocacy of representatives of neoliberal thoughts about private property, freedom of choice, as well as political and economic freedom, practice has failed to verify the theory because neoliberalism requires a strong state. By supporting authoritarian and dictatorial regimes, the advocates of this ideology actually approached the totalitarian system instead of opposing it. Does neoliberalism jeopardize democratic principles? Has neoliberalism made a step forward in social relations or has it taken us back and how did it come to this? The questions are to which the author of the text will try to answer.